“Monsieur Cannibale”, monstruo invisible de la violencia (Andamios, Revista de Investigación Social, 2011)
Freud’s symbolical interpretation of the “cannibal” in Totem and Taboo allows a new reading of violence against women, in the line of Fedullo works. Not disregarding other lines of interpretation, this one lights up the ways by which culture builds up its “monsters”.
Keywords: Violence; gender; symbolism; cannibal; monstrous